2001
DOI: 10.1046/j.1365-2257.2001.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of peripheral blood stem cells by the Sysmex SE-9500

Abstract: The Sysmex SE-9500 automated haematology analyser provides an estimate of immature cells, referred to as 'haematopoietic progenitor cells' (HPC). The aim of this study was to evaluate the reliability and usefulness of the SE-9500 HPC parameter as compared with the CD34 + cell count and to determine whether the HPC count was of value in predicting the optimal harvesting time for peripheral blood stem cells (PBSC). Studies were performed on 112 samples from 21 patients with haematological malignancies and 13 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 10 publications
4
20
0
2
Order By: Relevance
“…On the other hand, HPC counts were about fourfold lower than CD34+ cell counts in CD34 selected apheresis preparations; these results were comparable to those recently observed by Peng et al (Peng et al 2001). The precise nature of the progenitors measured in the HPC channel is unclear.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, HPC counts were about fourfold lower than CD34+ cell counts in CD34 selected apheresis preparations; these results were comparable to those recently observed by Peng et al (Peng et al 2001). The precise nature of the progenitors measured in the HPC channel is unclear.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we demonstrated that there was a good correlation between the numbers of HPCs and CD34 + cells in samples from not only the PB but also apheresis products. The correlation coefficient was much closer to 1.0 with this novel XN‐determined HPC count than with the previous SE/XE‐determined HPC count . These results suggested that the number of CD34 + cells in the final products could be predicted from the HPC count in the final products.…”
Section: Discussionsupporting
confidence: 48%
“…Clinical implications for peripheral blood progenitor cells collection where the decision to commence apheresis is modified by peripheral blood WBC, MNC, or HPC ture forms to be counted (19,26,27). Previous studies reported a strong correlation between PB HPC and PB CD34+ cell counts (25,28), and we have reported a strong correlation between HPC enumerated by Sysmex SE-9000 and CD34+ cells in the leukapheresis products from data on 32 patients (20). This strong correlation led us to investigate the clinical usefulness of HPC as a screening test to decide when to commence PBPC collection.…”
Section: Discussionmentioning
confidence: 99%